Integrated agronomy of pea (Pisum sativum L.): a review on cultivation, harvesting, and storage for sustainable agriculture - Zhang, Honglei; Sun, Hongyan; Tang, Zhong; Wang, Guoqiang (Frontiers in Plant Science, 2025)
Peas (Pisum sativum L.) are a cornerstone of sustainable agriculture, yet their potential is limited by fragmented agronomic practices. This review provides an integrated synthesis of advancements across cultivation, mechanized harvesting, and post-harvest storage. Key findings reveal that optimal growth conditions and nanotechnology interventions can significantly enhance abiotic stress tolerance. Mechanized harvesting innovations reduce yield losses by up to 40%, but smallholder adoption and terrain compatibility remain critical challenges. Effective post-harvest strategies, including low-temperature storage and hermetic bags, are crucial for preserving quality. Despite progress, systemic barriers persist. Future research must prioritize interdisciplinary solutions—combining genomics, precision engineering, and farmer training—to unlock the full potential of peas as a keystone crop for sustainable food systems.